Development of IT Systems for Ban Tak Hospital Services Using Hospital-Os Software: A Case Study at Tak Province - บัญญัติ พิเชฐ; รอดแสวง อภิชาติ; บัญญัติ สุภาภรณ์; โพธิ์ทอง รัชดา; อินภิรมย์ อัณณ์ฉัตร; โมราราช ภิพาภรณ์ (Journal of Health Science of Thailand, 2011)
The Hospital-Os software has been implemented in health services system of Ban Tak hospital. Tak province since 2004 with the objectives of improving health services performances. This article evaluated the approach of application, the results and key success factors of implementation of the Hospital-Os software in Ban Tak hospital. The participatory action research study was launched employing observation and interview of 15 members of committee on Information and Medical Records, 100 staffers and 30 clients in addition to a documentary research while using content analysis during 2001-2007 in 4 stages of the study; situation analysis, planning, implementation and evaluation Ban Tak hospital had its own approach to apply this software step by step and slow preparedness to adopt the software with the work flow in its context and improve the staffs’ capacity. The finding revealed that the Hospital-Os helped to improve health services system, performances and quality of services. It also minimized the flaws and risk in health services system, medication errors, patient’s right violation and waiting time. In conclusion, Hospital-Os software with leadership, team commitment, close cooperation of manager and staffs, doctors cooperation, on-call facilitators, relevance of software adaptation and staffs’ participation in improving software in implementation helped to improve results. Replication can only be made in other hospitals only when appropriate program setting and context are taken into account in parallel with thorough grasp of concepts and integration of the seven key success factors. The future Hospital-Os software needs to address optimal methods to tackle the problems, to increase the work flow coverage, to decrease the complexity of system and improve reporting system and to have long term evaluation with cost-effectiveness analysis.